2022
DOI: 10.3390/s22218497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an AI-Based TB AFB Smear Screening System for Laboratory Diagnosis on Routine Practice

Abstract: The most robust and economical method for laboratory diagnosis of tuberculosis (TB) is to identify mycobacteria acid-fast bacilli (AFB) under acid-fast staining, despite its disadvantages of low sensitivity and labor intensity. In recent years, artificial intelligence (AI) has been used in TB-smear microscopy to assist medical technologists with routine AFB smear microscopy. In this study, we evaluated the performance of a TB automated system consisting of a microscopic scanner and recognition program powered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Comparable concordance rates of 92.7% ( 16 ) and 95.7% ( 26 ) with MM have been described in recent studies evaluating other AI-powered automated AFB microscopy systems in high TB incidence settings. Interestingly, Tomasello et al observed a drop in sensitivity (from 97.0% to 70.7%) when a similar version of the MetaSystems’ AFB detection software was employed with assistance at a DNN PT of 50% ( 27 ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Comparable concordance rates of 92.7% ( 16 ) and 95.7% ( 26 ) with MM have been described in recent studies evaluating other AI-powered automated AFB microscopy systems in high TB incidence settings. Interestingly, Tomasello et al observed a drop in sensitivity (from 97.0% to 70.7%) when a similar version of the MetaSystems’ AFB detection software was employed with assistance at a DNN PT of 50% ( 27 ).…”
Section: Discussionmentioning
confidence: 63%
“…Meanwhile, with its current performance, detected AFB-smear-positive slides would require review by manual microscopy for confirmation and semi-quantification. The adoption of such technology within an established AFB testing algorithm could help streamline the use of molecular detection assays, where nucleic acid amplification tests would be reserved for AFB-smear-positive samples identified digitally ( 9 , 16 , 17 ). Overall, a-DM has the potential to improve laboratory productivity by allowing redistribution of the workforce particularly in high-throughput laboratories with low incidence TB.…”
Section: Discussionmentioning
confidence: 99%
“…The current study employed the N-acetyl-l-cysteine–NaOH (NALC–NaOH) technique to process specimens for both digestion and decontamination purposes [7] . Following centrifugation at 3200 × g for 20 min, the specimen was concentrated, and the precipitate was reconstituted with 0.067 Msterile phosphate buffer (pH 6.8).…”
Section: Methodsmentioning
confidence: 99%
“…However, the outcomes were categorized as AFB + or AFB-. Another assessment of an AI-based system for AFB detection was used in the same year 2022 by Hsiao et al in [27]. Each smear contained 200 images, which differed according to the WHO standard of at least 20-300 FoVs depending on tuberculosis level based on the IUATLD grades [31].…”
Section: Related Workmentioning
confidence: 99%
“…The CAD system can help pathologists to perform TB diagnostic smear microscopy more accurately and quickly. Two recent methods for sputum smear microscopy diagnosis have been developed to create CAD for TB: artificial intelligence (AI) [15], [22], [23], [24], [25] and mechanical automation [15], [26], [27], [28].These methods are similar to digital pathology, which uses an image recognition algorithm to detect AFB by digitally scanning the TB smear slides. These two combinations make the examination procedure more sensitive and accurate.…”
Section: Introductionmentioning
confidence: 99%